The Effectiveness Of The Cooperative Integrated Reading And Composition CIRC Learning Model On Student Learning Outcomes In Islamic Religious Education - Antika Antika; Baharudin Baharudin; Devi Sela Eka Selvia (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aims to analyze the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model on Islamic Religious Education (PAI) learning outcomes at SMP Negeri 36 Bandar Lampung. The study employed a quasi-experimental design with a post-test only control group. The sample consisted of an experimental class (CIRC) and a control class (conventional learning). The instrument consisted of 15 valid items with high reliability (α = 0.75) at the C4 cognitive level. The results indicate that the CIRC model significantly improves learning outcomes, particularly higher-order thinking skills, as well as enhances students’ participation and collaboration. The novelty of this study lies in the implementation of the CIRC model in Islamic Religious Education at SMP Negeri 36 Bandar Lampung. These findings suggest that CIRC is an effective alternative learning model to improve the quality of interaction, understanding, and higher-order thinking skills of students.